The Self-Pleasantness Judgment Modulates the Encoding Performance and the Default Mode Network Activity - Perrone-Bertolotti, Marcela; Cerles, Melanie; Ramdeen, Kylee T.; Boudiaf, Naila; Pichat, Cedric; Hot, Pascal; Baciu, Monica (Frontiers in Human Neuroscience, 2016)
In this functional magnetic resonance imaging (fMRI) study, we evaluated the effect of self-relevance on cerebral activity and behavioral performance during an incidental encoding task. Recent findings suggest that pleasantness judgments reliably induce self-oriented (internal) thoughts and increase default mode network (DMN) activity. We hypothesized that this increase in DMN activity would relate to increased memory recognition for pleasantly-judged stimuli (which depend on internally-oriented attention) but decreased recognition for unpleasantly-judged items (which depend on externally-oriented attention). To test this hypothesis, brain activity was recorded from 21 healthy participants while they performed a pleasantness judgment requiring them to rate visual stimuli as pleasant or unpleasant. One hour later, participants performed a surprise memory recognition test outside of the scanner. Thus, we were able to evaluate the effects of pleasant and unpleasant judgments on cerebral activity and incidental encoding. The behavioral results showed that memory recognition was better for items rated as pleasant than items rated as unpleasant. The whole brain analysis indicated that successful encoding activates the inferior frontal and lateral temporal cortices, whereas unsuccessful encoding recruits two key medial posterior DMN regions, the posterior cingulate cortex and precuneus. A region of interest analysis including classic DMN areas, revealed significantly greater involvement of the medial Prefrontal Cortex in pleasant compared to unpleasant judgments, suggesting this region’s involvement in self-referential (i.e., internal) processing. This area may be responsible for the greater recognition performance seen for pleasant stimuli. Furthermore, a significant interaction between the encoding performance (successful vs. unsuccessful) and pleasantness was observed for the posterior cingulate cortex, precuneus and inferior frontal gyrus. Overall, our results suggest the involvement of medial frontal and parietal DMN regions during the evaluation of self-referential pleasantness. We discuss these results in terms of the introspective referential of pleasantness judgments and the differential brain modulation based on internally- vs. externally-oriented attention during encoding.